Analysis of the Application of Co-Firing Using Sawdust–Coal on the Performance of PLTU 3 Banten Lontar - Fandhi Afriansyah; Ignatius Rendroyoko (Sean Institute, 2026)
This study analyzes the implementation of co-firing using sawdust in combination with coal at PLTU 3 Banten Lontar. The primary objective of this research is to evaluate the impact of co-firing application on power plant performance, thermal efficiency, exhaust gas emissions, and the cost of electricity production (BPP). The research method employed was an experimental approach, comparing 100% coal combustion with a fuel mixture consisting of 95% coal and 5% sawdust, conducted at PLTU Banten Lontar. The results indicate that the implementation of co-firing reveals a non-linear relationship between the 5% sawdust blending ratio and the composition of electrical energy generated. Furthermore, the application of co-firing reduced the cost of electricity production by IDR 46.45/kWh and successfully decreased CO₂, SO₂, and NOx emissions. Specifically, CO₂ emissions were reduced by 8.82%, SO₂ emissions decreased by 17.3%, and NOx emissions declined by 8.5%. The implications of this study suggest that co-firing can serve as a more environmentally friendly and cost-effective alternative for the power generation sector, with the potential for broader implementation in other coal-fired power plants across Indonesia.